O ensino de língua portuguesa: em pauta o processo de transposição didática do conceito de gênero do discurso para livros didáticos do ensino fundamental - Camelo, Antonio Carlos Bezerra (2016)
This master's degree paper, developed under the Postgraduate Program in Linguistic Studies ofFederal University of Uberlândia, proposes to reflect upon the statute ofPortuguese language teaching in Brazil, in two ways: i) by aiming at understanding the way in which the official teaching proposalis outlinedat present; ii) by intending to intervene to some extent on this statute, since it seeks to reflect/analyze the relationship between this proposal, present in two of its official documents and one of its didactic instruments, namely the textbook. More specifically, the main purpose of this study isto verify how two of the better evaluated collections by the National Textbook Program- 2014(Programa Nacional do Livro Didático - PNLD 2014) conducted, in the reading activities, the didactic transposition ofthe speechgenres notion, a central concept in contemporary Portuguese Language (PL) teaching proposals. This paper is based on Mikhail Bakhtin's theoretical framework, especially on his postulations around the notion of speech genres, according to which: Language is realized in the form of individual concrete utterances (oral and written) by participants in the various areas of human activity. These utterances reflect the specific conditions and goals of each such area not only through their content (thematic) and linguistic style, that is, the selection of the lexical, phraseological, and grammatical resources of the language, but above all through their compositional structure. All three of these aspects-thematic content, style, and compositional structure - are inseparably linked to the whole of the utterance and are equally determined by the specific nature of the particular sphere of communication. Each separate utterance is individual, of course, but each sphere in which language is used develops its own relatively stable types of these utterances. These we may call speech genres. (BAKHTIN, 1986 p.60) Taking as a starting point the definition of speech genres, central in the elaboration of the most current documents and proposals on Portuguese language teaching in Brazil, this research aims to verify if the textbooks best rated by the Portuguese Language Textbooks Guide - 2014 (Guia de Livro Didático de Língua Portuguesa – GLD 2014) really proposes forms of theoretical-methodological alignment with the foundations of the Bakhtinian proposal.The hypothesis of this research is that the notion of speech genres, when transposed from the theoretical universe of a field of knowledge to the universe of teaching -subject to the problems of education and scientific dissemination - has its socio-historical nature concealed. The analysis corpus is composed of two excerpts of texts from two collections of Portuguese Language Textbooks entitled Willingness to learn and Weaving Languages (Vontade de saber- 2012andTecendo Linguagens- 2012). The analysis will focus on reading activities carried out in two specific speech genres, namely autobiography and diary, both produced and put into circulation in the same sphere of activity, which we will classify as a sphere in which the genres are produced from the confluence between "history and memory". In this work, the delimitation of this sphere is based on the works of Schneuwly & Dolz (2004) and Mussalim (2004). The books in which the texts that will be analyzed appear are destined, respectively, to students of 6th and 7th grades of elementary school. It is worth clarifying that the corpus delimitation resulted from the observation of numerous units of didactic materials, and the two reading activities analyzed are being taken as emblematic of the reading work that is carried out in these books.